Games for training, education, health and sports : 4th International Conference on Serious Games, GameDays 2014, Darmstadt, Germany, April 1-5, 2014. Proceedings - Wiemeyer, Josef; Gobel, Stefan (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 4th International Conference on Serious Games for Training, Education, Health and Sports, GameDays 2014, held in Darmstadt, Germany, in April 2014. The 13 full papers presented together with 3 short papers, 2 keynotes, and 3 workshop papers were carefully reviewed and selected for inclusion in this book. The topics of the papers are settled in the fields of (game-based) training, teaching and learning, authoring tools, mobile gaming, health and rehabilitation, and citizen science. The papers address a broad scope of issues, including mechanisms and effects of (Serious) Games, adaptation and personalisation, local, mobile, and internet learning and education applications, game, reuse and evaluation, game settings, types of learners, problem solving etc.